« Petty treason » dans son contexte : genre et verdicts dans les procès pour meurtre entre conjoints aux assises du tribunal d’Old Bailey à Londres, Angleterre, 1674-1790 - Andrea McKenzie (Les Cahiers de Framespa)
This article analyses the trials of women charged with husband murder, a form of “petty treason”: a crime which theoretically struck at the heart of the social and gender hierarchy, and was subject to the horrific aggravated punishment of death by burning at the stake. We will see that in practice, however, the seventeenth- and eighteenth-century London courts tended to treat petty treason like any other homicide, with attenuating factors such as provocation and good character taken into account and often leading to manslaughter verdicts or acquittal. This article aims to shed light on the experience of women accused of spouse murder by placing them in a larger context, comparing their trials to those of men accused of murdering wives or common-law partners, and exploring the relationship between gender, class and credibility, verdicts and ultimate punishments.